Health Information Access for Deaf Yogyakarta Communities Through A Salutogenic Perspective - Ramania, Ardhina; Ristiyanti, Sinta; Muqarohmah, Nia Lestari (Jurnal Promkes: The Indonesian Journal of Health Promotion and Health Education, 2026)
Background: Access to health information remains a major challenge for the Deaf community in Indonesia due to the limited availability of inclusive and accessible media. Existing health information materials rarely use sign language and often rely on written or spoken formats that many Deaf individuals find difficult to fully understand. As a result, the Deaf community faces greater vulnerability to chronic diseases and mental health problems. This study aimed to contribute to the development of inclusive health information for the Deaf community in Yogyakarta by examining their lived experiences and identifying their needs and preferences in accessing health information through a salutogenic lens. Methods: A qualitative design was employed, involving in-depth interviews with four Deaf participants who were actively engaged in local Deaf communities. The interviews were conducted with the assistance of a sign language interpreter and were thematically analyzed using the salutogenic model. Member checking and peer debriefing were applied to enhance data validity. Results: The study identified substantial barriers to accessing health information, such as limited use of sign language, advanced or technical language in media, and the lack of subtitles or interpreters in videos. Social media emerged as the primary channel for accessing health information, with participants strongly preferring visual formats that combined sign language interpreters, subtitles, and engaging visuals. Reproductive health and mental health were identified as the most needed and relevant topics for the Deaf community. Conclusion: The findings highlight the urgent need to develop inclusive health information media that are tailored to the communication needs of Deaf individuals. Actively involving the Deaf community in the design and dissemination of health information helps create an enabling and inclusive environment that supports a salutogenic approach. Such efforts can reduce information inequities, improve health literacy, and ensure that health promotion strategies are accessible, relevant, and meaningful for Deaf communities.